Placental Findings in Postpartum Preeclampsia: A Comparative Retrospective Study - Ditisheim, Agnès; Sibai, Baha; Tatevian, Nina (American Journal of Perinatology, 2019)
Objective Preeclampsia is a multifactorial placental disease that can occur after delivery. The pathophysiology of postpartum preeclampsia remains unknown. The objective was to describe placental findings in postpartum preeclampsia.Study Design This is a case–control study, comparing the placental histologic findings in four groups of 30 patients with postpartum preeclampsia, early-onset preeclampsia, late-onset preeclampsia, and normotensive controls.Results Placentas of postpartum preeclampsia had a mean placental weight not different from that of late-onset preeclampsia at a similar gestational age (479.0 ± 152.7 vs. 521.3 ± 144.1 g, p = 0.07); they showed a higher rate of acute deciduitis of 42.4% than early preeclampsia (5.7%, p < 0.01) or in controls (3.2%, p < 0.01); 18.2% had decidual arteriolopathy, with no significant difference with other groups. These placentas had fewer villous infarcts as compared with early preeclampsia (9.1 vs. 62.9%, p < 0.01) and less accelerated maturation of villi (24.2 vs. 74.3%, p < 0.01).Conclusion There were no significant differences for decidual arteriolopathy and villous infarcts among postpartum preeclampsia, late-onset preeclampsia, and the controls. This suggests that postpartum preeclampsia is more of a maternal disease in which the placenta may act as a priming effect in predisposed mothers and becomes clinically apparent after delivery.
Keywords: postpartum period; preeclampsia; pregnancy; hypertension; placental findings; placental disease